PEMBANGUNAN JARINGAN JALAN PERKOTAAN BERDASARKAN KAJIAN STRUKTUR RUANG DAN AKSESIBILITAS KOTA - Masrianto, Masrianto; Poerwo, Poernomosidhi; Soetomo, Soegiono; Riyanto, Bambang (Jurnal Transportasi, 2012)
This paper presents the concept of a simple model to investigate the effects of land use change to accessibility. The proposed model consists of three interrelated stages submodel. The application of the model in the case of Semarang showed that residential area is most dominant zone forming the structure ofurban space, followed by the commercial and industrial zones. Related to the price of land, there is a difference in the land use and accessibility changes at 2 different time periods. Changes in the structure of space associated with an increase in land prices could affect the accessibility of the zone due to the potentialzone with high urban land price change. The concept of this model can be used as a theoretical basis for urban planners in Indonesia and is expected to be to be used as a tool to make a decision for the sustainable planning policy makers a road network in urban areas in developing countries such as Indonesia.Keywords: land use, accessibility, the structure of urban space.